(untitled) - Richards, Jack C. (New York, 2011)
This second level of a three-level series that gives intermediate students who have studied English previously extensive practice in understanding everyday conversational language. There are 24 unit lessons accompanied by tactics for testing materials to assist students with the listening sections of the TOEIC test, the TOEFL test, IELTS, and other exams
Keywords: English language,Tiếng Anh; Sách giáo khoa cho người nước ngoài